The Effect of Sensoric Marketing on McDonald's Consumer Repurchase Intention in Bandar Lampung City with Customer Satisfaction as Mediation Variable - Hilmi Aunillah Kamil; Aida Sari; Dwi Asri Siti Ambarwati (International Journal of Scientific Multidisciplinary Research, 2023)
People are eating differently now; they like quick and easy meals. Only in Indonesia are there a lot of fast food restaurants. One of the main fast food chains that has market dominance in Indonesia is McDonald's. In Indonesia, McDonald's built many locations, including Bandar Lampung. The findings of the Google review section reveal that many McDonald's patrons in Bandar Lampung are still not happy with their sensory encounter there. In this study, the mediating variable is satisfaction, which is used to explore how sensory marketing affects consumer repurchase intentions. Based on the questionnaire of 250 respondents, it has been shown that both customer satisfaction and sensory marketing have a favorable and considerable influence on consumers' intentions to make more purchases. Additionally, there is a positive and significant association between sensory marketing and repurchase intention, with satisfaction acting as a mediating component